Św. Augustyn, jego życie moralne i duchowe w autowypowiedziach w "Enarrationes in psalmos" - Wojda, Jacek (Vox Patrum, 2013)
St. Augustine, beside his typically autobiographical work – Confessiones, left a number of statements about himself in his many writings, among which the outstanding place is taken by his Enarrationes in Psalmos. By reflecting on the person of St. Augustine, through the prism of his statements in Enarrationes in Psalmos, one can reveal and realize the great richness of what regards his moral and spiritual life. Augustine, being a priest, then a bishop, and fulfilling the office of preacher, refers to his life from before his conversion, recalls his baptism, and analyzes his commitment to the new way of life. His conversion and baptism are of particular importance by driving him from one stage of life to the other. This second phase of his biography, however, does not cancel out some struggles with worldly temptations and various adversities in pastoral ministry. The leading of „perfect” life is embodied in the work of God’s mercy. Confessiones efficiently assist to discover Augustine of Enarrationes in Psalmos, who reveals his heart and his person for the benefit of people entrusted to his pastoral care.